2021
DOI: 10.3390/polym14010071
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of 2-Amino-7-Fluorophenazine 5,10-Dioxide Polymeric Micelles as Antitumoral Agents for 4T1 Breast Cancer

Abstract: 2-Amino-7-fluorophenazine 5,10-dioxide (FNZ) is a bioreducible prodrug, poorly soluble in water, with potential anticancer activity on hypoxic-tumors. This poor solubility limits its potential applications in clinic. Amphiphilic pristine polymeric micelles (PMs) based on triblock copolymers Pluronic® and Tetronic®, glycosylated derivatives and their mixtures with preformed-liposomes (LPS), were analyzed as strategies to improve the bioavailability of FNZ. FNZ encapsulations were performed and the obtaining nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…Furthermore, the 7‐fluoro‐2‐aminophenazine‐PDO ( 6 ) displayed in vitro bioreductive selective cytotoxicity towards solid tumors in hypoxic regions [75] . Some in vivo preclinical studies carried out in BALB/c female mice bearing 4T1‐breast‐tumor as a murine model confirmed its antitumor activity by the quantification of a decrease in tumor size, animals’‐survival, and biochemical/hematological data [56] . The combination of PDO derivatives with an incorporated benzyl group, e. g ., 7(8)‐bromo‐2‐(4‐nitrobenzyloxy)‐PDO, 7(8)‐bromo‐2‐(4‐chlorobenzyloxy)‐PDO and 7(8)‐bromo‐2‐(4‐methylthiobenzyloxy)‐PDO ( 7 ) are new selective hypoxic cytotoxins with additional ability to inhibit DNA topoisomerase II activity [57] .…”
Section: Phenazine N5n10‐dioxide Derivativesmentioning
confidence: 96%
See 3 more Smart Citations
“…Furthermore, the 7‐fluoro‐2‐aminophenazine‐PDO ( 6 ) displayed in vitro bioreductive selective cytotoxicity towards solid tumors in hypoxic regions [75] . Some in vivo preclinical studies carried out in BALB/c female mice bearing 4T1‐breast‐tumor as a murine model confirmed its antitumor activity by the quantification of a decrease in tumor size, animals’‐survival, and biochemical/hematological data [56] . The combination of PDO derivatives with an incorporated benzyl group, e. g ., 7(8)‐bromo‐2‐(4‐nitrobenzyloxy)‐PDO, 7(8)‐bromo‐2‐(4‐chlorobenzyloxy)‐PDO and 7(8)‐bromo‐2‐(4‐methylthiobenzyloxy)‐PDO ( 7 ) are new selective hypoxic cytotoxins with additional ability to inhibit DNA topoisomerase II activity [57] .…”
Section: Phenazine N5n10‐dioxide Derivativesmentioning
confidence: 96%
“…[75] Some in vivo preclinical studies carried out in BALB/c female mice bearing 4T1-breast-tumor as a murine model confirmed its antitumor activity by the quantification of a decrease in tumor size, animals'survival, and biochemical/hematological data. [56] The combination of PDO derivatives with an incorporated benzyl group, e. g., 7(8)-bromo-2-(4-nitrobenzyloxy)-PDO, 7(8)-bromo-2-(4-chlorobenzyloxy)-PDO and 7(8)bromo-2-(4-methylthiobenzyloxy)-PDO (7) are new selective hypoxic cytotoxins with additional ability to inhibit DNA topoisomerase II activity. [57] Hernández et al [58] showed the chemosensitizer effect of the PDO analogs such as 8 to cisplatin and the mechanism of action on bladder cancer cells.…”
Section: Phenazine N 5 N 10 -Dioxide Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In particular, there has been a great increase in the use of pristine block copolymers, Pluronic® and Tetronic®, for tumour diagnosis and therapy, in response to their FDA approval. [16][17][18][19] Notable features are their unique aqueous selfassembly properties and core-shell structure based on amphiphilic copolymers formed by one hydrophobic backbone of poly( propylene oxide) (PPO), flanked by hydrophilic poly(ethylene oxide) (PEO) chains, [16][17][18] which can be advantageous when ICG is used for molecular cancer diagnosis. Chiefly, we have found that PMs preferentially accumulate in solid tumours and capitalize on their characteristics, such as the high vascularization, poor lymphatic clearance, and slow venous return, via the enhanced permeability and retention (EPR) effect that has been widely reported in different nanosystems.…”
Section: Introductionmentioning
confidence: 99%